1999
DOI: 10.1046/j.1365-2796.1999.00495.x
|View full text |Cite
|
Sign up to set email alerts
|

Adrenoceptor genes in human obesity

Abstract: The genes causing obesity in rodent models have been characterized, but do not seem to be important for human obesity. Recently the putative association between obesity and polymorphism in human betaadrenergic receptor genes have been studied intensely in the light of the important role of these receptors in the regulation of energy mobilization and utilization. A polymorphism (Trp64Arg) in the beta 3 -adrenergic receptor gene is associated with obesity (relative risk < 2) in some but not all investigations on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
90
0
3

Year Published

2005
2005
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(96 citation statements)
references
References 45 publications
(56 reference statements)
3
90
0
3
Order By: Relevance
“…The ability of some people to increase energy Resting metabolic rate and body weight gain S Buscemi et al expenditure in response to an increased energy intake and vice versa is probably a genetic characteristic [13][14][15] that might be mediated by different mechanisms such as sympathetic activity or b 3 receptors, uncoupling protein, brown adipose tissue activity or other systems. [16][17][18] Ravussin suggested normalizing RMR for FFM, taking into consideration the positive intercept in the linear regression between the two variables. 11 However, the same conclusions were reached, even when the procedure of normalizing RMR for FFM was followed.…”
Section: Discussionmentioning
confidence: 99%
“…The ability of some people to increase energy Resting metabolic rate and body weight gain S Buscemi et al expenditure in response to an increased energy intake and vice versa is probably a genetic characteristic [13][14][15] that might be mediated by different mechanisms such as sympathetic activity or b 3 receptors, uncoupling protein, brown adipose tissue activity or other systems. [16][17][18] Ravussin suggested normalizing RMR for FFM, taking into consideration the positive intercept in the linear regression between the two variables. 11 However, the same conclusions were reached, even when the procedure of normalizing RMR for FFM was followed.…”
Section: Discussionmentioning
confidence: 99%
“…32 However, several studies found the maximal activation potential of cyclic AMP (adenosine 3 0 ,5 0 -cyclic monophosphate) in Arg variant cells was reduced, suggesting the substitution may alter the receptor's ability to interact with G protein. [31][32][33] In clinical studies, a significant reduction in receptor sensitivity to a beta3-agonist was found in adipocytes of Arg carriers, 34 whereas two studies observed no association with basal metabolic rate. 35,36 The ADRB3 receptor is more abundant and active in visceral adipose tissue than subcutaneous adipose.…”
Section: Adrb3 and Obesity R Mckean-cowdin Et Almentioning
confidence: 99%
“…31 The tryptophan-toarginine substitution at codon 64 of ADRB3 was initially reported in 1995. 13,15,24 The substitution is located in the first coding exon, at the junction of the first transmembrain domain and the first intracellular loop of the receptor.…”
Section: Adrb3 and Obesity R Mckean-cowdin Et Almentioning
confidence: 99%
“…54 Later studies have reported inconsistent results with respect to the Trp64Arg variant and diabetic and obesity phenotypes. [55][56][57] More recently, the Trp64Arg polymorphism was suggested to interact with obesity in conferring risk of pre-eclampsia with the rarer Arg64 variant being possibly protective against pre-eclampsia in overweight women. 47 As the pharmacogenetic data on ADRB3 polymorphisms are less developed than those for ADRB1 and ADRB2, the remainder of this review will concentrate on the latter two receptors.…”
Section: Adrb3 Polymorphismsmentioning
confidence: 99%